MEKANISME KETAHANAN KENTANG (SOLANUM TUBEROSUM) TERHADAP NEMATODA SISTA KUNING (GLOBODERA ROSTOCHIENSIS) (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Resistance mechanism of potato (Solanum tuberosum) to golden cyst nematode (Globodera rostochiensis).  The research was conducted from June 2005 to May 2006 in Kepuhharjo, Cangkringan, Sleman, Yogyakarta. The aims of the research were to find the resistance status of 20 potato varieties, role of  chlorogenic acid and caffeic acid  in the resistance mechanism and histopathological differences between resistant and susceptible potato varieties to  G. rostochiensis. The results showed that two varieties were resistant to G. rostochiensis, i.e, Hertha and Manohara.  Thirteen varieties were moderately resistant, i.e; No.30, No.44, No. 5, No.19, Batang Hitam, Agria,  Desiree, Berolina, Atlantik, No.095, Cipanas, FLS and Colombus, and five varieties were susceptible, i.e; Kikondo, Granola, Erika, LBR, and Fries. The presence of chlorogenic acid and caffeic acid in Hertha (resistant variety) and in Granola (susceptible variety) were analized by TLC. In Hertha chlorogenic acid was detected at 4, 5, and 6 days after inoculation (DAI), whereas in Granola it was detected at 1 and 6 DAI. It was assumed that the presence of chlorogenic acid for 3 successively week in Hertha, caused it more resistant than Granola.  Cell lignification inhibited                       G. rostochiensis grow well inside the root tissue of Hertha, whereas in Granola only a few cell was lignified as indicated by less absorption of red colour (safranin) in infected areas. Caffeic acid was not detected either in uninoculated or inoculated of both potato varieties.  It indicated that caffeic acid might not be naturally present in Hertha and Granola and nematode infection could not stimulate the production of this compound.